Effectiveness of different acne treatment methods: a comparison of pharmacological, procedural and natural therapies - Nojek, Paweł; Pawlik, Wiktoria; Zimonczyk, Mariusz; Zawół, Monika; Błaszczyński, Gustaw; Nowotarska, Agnieszka (Journal of Education, Health and Sport, 2024)
Acne vulgaris is a chronic skin condition affecting millions of people, especially adolescents. This study analyzes the effectiveness of various acne treatment methods, including pharmacological, procedural, and natural therapies. It compares their mechanisms of action, therapeutic effects, and potential side effects. The aim of this study is to identify the most effective therapeutic strategies to improve patients’ quality of life and mental health. The analysis results suggest that a comprehensive approach to acne treatment, combining different methods, may yield the best outcomes.